Epigenetic and genetic components of height regulation - Stefania Benonisdottir (Nature Portfolio, 2016)
Adult height has a strong genetic component and is highly heritable. Here the authors whole-genome sequence 8,453 Icelanders and find novel parent-of-origin derived associations in IGF2-H19 and DLK1-MEG3.